Vsebnost klora v lesnih ostankih slovenske pohištvene industrije - Humar, Miha (Les (Ljubljana), 2010)
After implementation of Slovenian governmental ordinance on transformation of nonhazardous wastes to solid fuels, high chlorine concentrations in wooden residues cause considerable difficulties to wooden manufacturing companies when using those residues for energetic purposes. Therefore reasons for chlorine contamination were elucidated.
Keywords: les; lesni ostanki; onesnaževanje okolja; klor